The films that made me: essays and reviews from The Guardian - Bradshaw, Peter, (Bloomsbury Caravel, 2019)
"'Like a pizza delivery driver who travels everywhere by moped, or a volcanologist who keeps turning the central heating up, I'm a film critic who loves going to the cinema.' Peter Bradshaw is the film reviewer for intelligent, curious cinemagoers; he has worked at the Guardian for twenty years. The Films That Made Me collates his finest reviews from the last two decades, which carry with them his deep experience, knowledge and understanding of film. Introducing each section with a brief introductory article in his light, humorous tone, and ranging from The Cat in the Hat and the Twilight Saga to Synecdoche: New York, Bradshaw shares the films that he loved, the films that he hated, the films that made him laugh, cry, swoon and scared. Bradshaw's reviews range from the insightful and introspective to the savage and funny. The Films That Made Me is a must read for all film fanatics." -- provided by publisher
https://katalog.adlr.link/Record/155-1757168680